Plantar Medial Avulsion Fragment Associated With Tongue-Type Calcaneus Fractures. (June 2019) - Adams, Mark R.; Koury, Kenneth L.; Mistry, Jaydev B.; Braaksma, William; Hwang, John S.; Firoozabadi, Reza
Background: The plantar fascia attaches to the tuberosity of the calcaneus, which produces a distinct plantar medial avulsion (PMA) fracture fragment in certain calcaneal fractures. We hypothesized that tongue-type fractures, as described by the Essex-Lopresti classification, were more likely to be associated with this PMA fracture than joint depression fractures. Methods: A retrospective chart review was performed at 2 distinct Level I trauma centers to identify patients sustaining calcaneal fractures. Radiographs were then reviewed to determine the Essex-Lopresti classification, OTA classification, and presence of a PMA fracture. Results: The review yielded 271 total patients with 121 (44.6%) tongue-type (TT), 110 (40.6%) joint depression (JD), and 40 (14.8%) fractures not classifiable by the Essex-Lopresti classification. In the TT group, 73.6% of the patients had the PMA fracture whereas only 8.2% of JD and 15.0% of nonclassifiable fractures demonstrated a PMA fragment ( P < .001). Conclusion: Plantar medial avulsion fractures occurred in 38.4% of the calcaneal fractures reviewed with a significantly greater proportion occurring in TT (73.6%) as opposed to JD (8.2%). Given the plantar fascia attachment to the PMA fragment, there may be clinical significance to identifying this fracture and changing treatment management; however, this requires further investigation. Level of Evidence: Level III, comparative study.